Salvia officinalis extract in the treatment of mild to moderate Alzheimer's Disease: A placebo-controlled, randomized and double blind clinical trial. - Sh Akhondzadeh; M Norouzian; MR Mohammadi; S Ohadinia; AH Jamshidi; M Khani (Institue of Medicinal Plants, ACECR, 2002)
New treatments were presented for management of Alzheimer's Disease (AD) in the recent years. However, they were not fully successful. The objective of this study was to assess the efficacy and safety of Salvia officinalis extract in AD at 4 months using fixed dose of the extract. A randomized, double blind, placebo-controlled trial in three centers in Iran was the structure of this study. Patients with mild to moderate AD (n=36, 10 women) with a score of ≤ 12 on the cognitive subscale of Alzheimer's Disease Assessment (ADAS-cog) and ≤ 2 on Clinical Dementia Rating (CDR) were randomized to placebo or fixed dose of Salvia officinalis extract. Over 16 weeks, the primary outcome measure was the change in ADAS-cog score. Change in CDR (sum of the boxes) was the secondary outcome over the trial. At 4 months, Salvia extract produced a significant better outcome on cognitive function and CDR total score than placebo (ADAS-cog: d.f.: 1 f = 4.77, P = 0.037) (CDR: d.f.: 1, F=10.84, P<0.003). There were no significant differences in the two groups in terms of observed side effects. The present study indicates that patients on Salvia officinalis extract compare with those on placebo experienced benefits in cognitive function and basic activity of daily living. However, further studies are warranted.